Laboratory evaluation of compactability and performance of warm mix asphalt (2012)
Warm mix asphalt (WMA) is the term used to describe the set of technologies that allow fabrication of asphalt mixtures at lower temperatures than those specified for conventional hot mix asphalt (HMA). This temperature reduction leads to advantages, compared to construction of HMA, that include energy savings, reduced emissions, and safer working conditions. However, WMA is a relatively new technology and several aspects are still under evaluation. This paper assesses some of these aspects including laboratory compactability and its relation to mixture design, and performance of WMA (i.e., permanent deformation and cracking resistance) fabricated with three WMA additives, namely Advera®, Sasobit®, and Evotherm®. Corresponding results showed better or equivalent laboratory compactability for the WMA, as compared to that of the HMA used as reference (or control-HMA), leading to smaller optimum asphalt contents selected based on a specific target density (i.e., 96%). In terms of performance, inclusion of the WMA additives led to decrease the mixture resistance to permanent deformation, althought